Knowledge, attitude and perceptions of pharmacists regarding renal dose adjustment among chronic kidney disease patients in Pakistan - Zafar, Roheena; Rehman, Inayat Ur; Shah, Yasar; Ali, Zahid; Long, Chiau Ming *; Khan, Tahir Mehmood (Taylor and Francis Group, 2023)
Background: Chronic kidney disease (CKD) poses a significant public health challenge. CKD patients have compromised renal function, which not only alters the pharmacokinetics of drugs but also their pharmacodynamics. Adjusting drug doses for these patients is essential to achieve the intended clinical outcomes, prevent adverse drug events, and halt further progression of the disease. Pharmacists play a pivotal role in ensuring safe and appropriate therapy for CKD patients. However, there is a noticeable absence of national dosing guidelines for CKD in Pakistan, coupled with a scarcity of studies exploring the knowledge, attitude, and perception of renal dose adjustments in the country. This study aimed to evaluate the knowledge, attitudes, and perceptions of pharmacists in the Khyber Pakhtunkhwa province and Islamabad regarding renal dose adjustments.